2010
DOI: 10.21608/jppp.2010.86972
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Sweet Sorghum Genotypes to Stem Corn Borers Resistance With Presence of Morphological and Chemical Characters

Abstract: This work was conducted in the Agricultural Experimentation Center, Faculty of Agricultural, Al-Azhar University, Assiut Branch, during two successive seasons 2007 and 2008. Fifty three genotypes of sweet sorghum (Sorghum bicolor.L) were screened to find out how much each of the resistance variables affects the genotypes resistance against corn and sugar cane borers namely, (Sesamia cretica. Ledder and Chilo agamemnon.Bleszyncki.). The tested trits were plant height, leaves number and number of days to 50 % fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…The current results agreed with those obtained by AbdEl-Raheem et al (2010),Khidr et al (2021), andYücel et al (2022) who found obvious differences among tested genotypes in brix percentage. With respect to sucrose % content, three genotypes (Rona, SS405, and Roma) were found to be outperformed the remainder of tested sweet sorghum genotypes in this study recording more than 11 % where the lowest sucrose % values (less than 9 %) were obtained by Willy, Dall, GK Ahron and Sugar drip genotypes showing the possibility of participation of these genotypes in the breeding program of sorghum crop to improve the sugar content(Rao et al, 2013 andErdurmus et al, 2018).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The current results agreed with those obtained by AbdEl-Raheem et al (2010),Khidr et al (2021), andYücel et al (2022) who found obvious differences among tested genotypes in brix percentage. With respect to sucrose % content, three genotypes (Rona, SS405, and Roma) were found to be outperformed the remainder of tested sweet sorghum genotypes in this study recording more than 11 % where the lowest sucrose % values (less than 9 %) were obtained by Willy, Dall, GK Ahron and Sugar drip genotypes showing the possibility of participation of these genotypes in the breeding program of sorghum crop to improve the sugar content(Rao et al, 2013 andErdurmus et al, 2018).…”
supporting
confidence: 92%
“…Results in Table3revealed that genotypes; Willy, William, and Atlas out yielded high values of juice extraction % (34.28, 39.82, and 4.69 %) and juice yield (4.87, 5.24 and 4.69 ton/fed), respectively indicating their magnitude as promising genotypes that may be used in breeding programs of sweet sorghum. The current results are harmonized with many previous investigations reported byAbd El-Raheem et al (2010),Rao et al (2013),Erdurmus et al (2018),Mulima et al (2018),Khidr et al (2021) andYücel et al (2022) who confirmed that the considerable variability among the assessed sweet sorghum genotypes considering the juice quality readings provides a real chance to improve the juice productivity of sweet sorghum crop and its extracts and other products.…”
supporting
confidence: 91%